Analisis Kebijakan Luar Negeri Qatar dalam Negosiasi Taliban-Amerika Serikat (2018-2019) - Zhahirah, Amirah (Jurnal ICMES, 2024)
On August 15, 2021, the United States and its allies withdrew from Afghanistan, followed by the return of the Taliban to power. The withdrawal was part of the Doha Agreement, which was the result of US-Taliban negotiations with Qatar as a mediator. This study aims to analyze Qatar's foreign policy and explain the goals, objectives, options, consequences, and choices behind Qatar's decision to mediate the US-Taliban negotiations. This study uses a qualitative research method. The results of this study indicate that the goals and objectives of Qatar's foreign policy are to secure itself from threats from the Gulf countries and to strengthen its political existence. This decision was taken after considering the options and their consequences. The first option is to sever ties with the Taliban with the consequence that the Taliban will not agree to negotiate with the United States. The second option is to become a mediator for the US-Taliban with the consequence that Qatar increases its regional presence while receiving protection from the United States from its neighboring countries.